1982
DOI: 10.1037/h0077894
|View full text |Cite
|
Sign up to set email alerts
|

Cortical substrates of taste aversion learning: Dorsal prepiriform (insular) lesions disrupt taste aversion learning.

Abstract: The functional relation between restricted damage to ventral primary somatosensory neocortex and the ability of rats to acquire conditioned taste aversions (CTA) was examined by a combination of behavioral and neurohistological techniques. Lesions confined exclusively to the established gustatory neocortex (GN) did not disrupt CTA acquisition, nor did lesions confined to suprarhinal cortical areas ventral to the GN. Lesions that encroached on dorsal prepiriform and insular cortices produced CTA acquisition def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 42 publications
5
48
0
Order By: Relevance
“…Thus, Experiment 3 tested whether these same lesions of the gustatory cortex also disrupt acquisition of a LiCl-induced conditioned taste aversion. As described, there are data in support of this possibility (Dunn & Everitt, 1988; Koh & Bernstein, 2005; Naor & Dudai, 1996; Ramirez-Amaya et al, 1996), and data that, either directly or indirectly argue against it (Flynn et al, 1991; Geddes et al, 2004; Geddes et al, 2003; Grigson, Lyuboslavsky et al, 2000; Lasiter & Glanzman, 1982; Mackey et al, 1986; Reilly & Pritchard, 1996a; Scalera et al, 1997; Zito et al, 1988). In the present study we used low (0.009 M) and standard (0.15 M) dose of LiCl because, when passively administered to intact rats, these doses suppress CS intake in a manner similar to the standard and higher doses of cocaine and morphine (Grigson, 1997).…”
Section: Methodsmentioning
confidence: 89%
“…Thus, Experiment 3 tested whether these same lesions of the gustatory cortex also disrupt acquisition of a LiCl-induced conditioned taste aversion. As described, there are data in support of this possibility (Dunn & Everitt, 1988; Koh & Bernstein, 2005; Naor & Dudai, 1996; Ramirez-Amaya et al, 1996), and data that, either directly or indirectly argue against it (Flynn et al, 1991; Geddes et al, 2004; Geddes et al, 2003; Grigson, Lyuboslavsky et al, 2000; Lasiter & Glanzman, 1982; Mackey et al, 1986; Reilly & Pritchard, 1996a; Scalera et al, 1997; Zito et al, 1988). In the present study we used low (0.009 M) and standard (0.15 M) dose of LiCl because, when passively administered to intact rats, these doses suppress CS intake in a manner similar to the standard and higher doses of cocaine and morphine (Grigson, 1997).…”
Section: Methodsmentioning
confidence: 89%
“…Although lesion studies have traditionally revealed a critical role for GC in CTA (see, e.g., Braun et al, ; Lasiter and Glanzman, ; Dunn and Everitt, ; Bermudez‐Rattoni and McGaugh, ; Nerad et al, ; Cubero et al, ; Fresquet et al, ; Roman and Reilly, ), several recent reports have questioned this attribution (Geddes et al, ; Hashimoto and Spector, , Schier et al, ; Blonde et al, ). Indeed, a previous study in rats from our laboratory failed to find evidence of CTA impairment following extensive damage in GC (Schier et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The overall conclusions are still debated, and the results appear to depend on the type of lesion (whether surgical ablation, electrolytic, cytotoxic, or metabolic lesion), its location within the amygdala, its duration (permanent vs. transient), and its timing relative to training and testing. Although some investigations revealed no significant effects of certain amygdala lesions on CTA (Kemble et al 1979;Hatfield et al 1992;Galaverna et al 1993), in most studies, amygdala lesions, especially of the basolateral nucleus (Fitzgerald and Burton 1983;Simbayi et al 1986;Yamamoto and Fujimoto 1991;Roldan and Bures 1994;Yamamoto et al 1995), but also including the CeA (Lasiter andGlanzman 1982 1985;Roldan and Bures 1994), disrupted acquisition of CTA, its retrieval, or both. Roldan and Bures (1994) suggested that amygdaloid nuclei subserve CTA in the intact brain, but that their permanent absence can be compensated for by other brain centers.…”
Section: Discussionmentioning
confidence: 99%